Struggle of meaning and the Jokowi Myth in the 2018 Asian Games Opening video - Ritonga, Rajab; Nugroho, Eko; Handoko, Daniel (Penerbit Universiti Kebangsaan Malaysia, 2019)
From a semiotics perspective, the Asian Games opening ceremony became a signifying image framed naturally by myth. Myths as a foreigner’s lackey, communist sympathizer, and anti-Islam have been cast virtually by anonymous political adversaries unto Joko Widodo (Jokowi) as one of Indonesia’s presidential candidates. This study discusses the myths underlying the meaning of Jokowi’s figure; how those myths developed meanings of images in the 2018 Asian Games Opening video; and how those myths became a struggle of meaning for Jokowi as the presidential candidate. This study employed the qualitative approach by using the critical paradigm. This is, thus, a research that attempts to develop elaborations concerning the concept and phenomenon of power and its practices, and it describes them to develop inductive explanation from the acquired data. Roland Barthes’ semiotics method is used in this study. The text analyzed is the content of Jokowi’s video during the 2018 Asian Games Opening ceremony. This research managed to produce a model for understanding the struggle of meaning involving myths and the construction of sign reality in the text display of the 2018 Asian Games opening video. The model indicates the struggle of meaning between the scripts of the ruler (the incumbent) and the myths attached within the public’s ideological frame of mind.